Temperature-induced structural evolution in liquid Sn85Zn15 eutectic alloy. (15th April 2018) - Chen, X.; Yu, Q.; Su, Y.; Wang, X.D.; Cao, Q.P.; Zhang, D.X.; Jiang, J.Z.
Abstract: Temperature-dependent atomistic structural evolution in liquid Sn85 Zn15 eutectic alloy has been investigated by using in situ high energy X-ray diffraction and ab initio molecular dynamics simulations. We reveal a structural crossover at around 900 K in liquid Sn85 Zn15 eutectic alloy, below and above which the liquids exhibit different changes in first peak position shifts on S ( q ) and G ( r ) curves, the nearest coordination number and activation energies for self-diffusion. This structural crossover is likely ascribed to the spatial connectivity variation of local clusters. Our finding will trigger more studies on the liquid-to-liquid structural transition in metallic liquids. Graphical abstract: